2021
DOI: 10.1021/acsanm.1c02369
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Organic Framework-Derived Porous Nanorods for Chemoselective Hydrogenation of Quinoline Compounds at an Aqueous/Oil Interface

Abstract: In this work, a Cu-BTC material was first synthesized by a hydrothermal rota-crystallization method using cupric nitrate and benzene-1,3,5-tricarboxylate (BTC) as raw materials. Compared with a conventional hydrothermal method, this route greatly shortened the synthesis time of Cu-BTC to only 2 h. Cu-BTC was then treated under a N 2 atmosphere at different times and temperatures to obtain the derivative Cu/C-x-t with exceptional hydrophobicity (WCA of 146°), where x represents the pyrolysis temperature and t w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…It can be clearly seen that when THF was added, the contact angle was close to 0°, indicating that the catalyst was lyophilic, so THF can well wet the catalyst with good wettability. Therefore, the good lipophilicity of the catalyst was beneficial to the dispersion of the catalyst in the solvent THF and the full contact with the substrate, thus promoting the catalytic reaction. …”
Section: Resultsmentioning
confidence: 99%
“…It can be clearly seen that when THF was added, the contact angle was close to 0°, indicating that the catalyst was lyophilic, so THF can well wet the catalyst with good wettability. Therefore, the good lipophilicity of the catalyst was beneficial to the dispersion of the catalyst in the solvent THF and the full contact with the substrate, thus promoting the catalytic reaction. …”
Section: Resultsmentioning
confidence: 99%
“…When methyl or amino groups appeared on the ring (entries 1–3), the conversion reached >98.0% and the selectivity was >96% . These results are due to the fact that the electron-donating groups stabilize the positive charge and favor the selective hydrogenation of the pyridine ring, thus leading to high activity and selectivity . When these groups were substituted with the electron-absorbing chlorine or nitro group (entries 4–6), the activity was relatively low.…”
Section: Resultsmentioning
confidence: 99%
“…These results are due to the fact that the electron-donating groups stabilize the positive charge and favor the selective hydrogenation of the pyridine ring, thus leading to high activity and selectivity. 61 When these groups were substituted with the electron-absorbing chlorine or nitro group (entries 4−6), the activity was relatively low. The conversion of 5-nitroquinoline was only 65.1%, and 2chloroquine had a conversion of 85.1% under more stringent reaction conditions (120 °C and 6 h); these results are because the fracture of the ring due to the electron-absorbing nitro and chlorine groups is unfavorable for the selective hydrogenation of the pyridine ring.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…A great number of studies showed that the carbon defects could produce unpaired p electrons, thereby promoting electron transfer and the adsorption of certain substrates, which may be one of the reasons why this material presented good catalytic performance in a series of catalysts. 37 Thermogram curves of Co/CN-x prepared at different pyrolysis temperatures are given in Fig. 6(b).…”
Section: Characterization Of Catalystsmentioning
confidence: 99%